The Simulated Cardiology Clinic: A Standardized Patient Exercise Supporting Medical Students' Biomedical Knowledge and Clinical Skills Integration - Jennifer M. Jackson; R. Brandon Stacey; Sharon S. Korczyk; Donna M. Williams (Association of American Medical Colleges, 2020)
Introduction Development of cardiac disease-related diagnostic skills-including hypothesis-driven data gathering, heart sound interpretation, and ECG interpretation-is an important component of medical student training. Prior studies indicate trainees' performance of these skills is limited. Simulation provides students with opportunities to practice integrating their developing knowledge in a relevant clinical context. We developed a simulated clinic activity for second-year medical students consisting of standardized patient (SP) cases representing cardiovascular (CV) diseases. Methods Student small groups rotated through four SP encounters. For each case, one student performed the history, after which the whole small group listened to audio files of heart sounds, interpreted an ECG, and collaboratively developed a prioritized differential diagnosis. The CV course director met with students for a large-group debrief, highlighting key learning points. We collected learners' evaluations of the event through an online survey. Results Of students, 276 participated in this activity over the course of 2 years. Nearly all students assessed the activity as extremely or quite effective for applying learning content from the CV course (97%, 2018; 93%, 2019), and for practicing how to approach chest pain, shortness of breath, palpitations, and fatigue (100%, 2018; 95%, 2019). The most helpful aspects were reinforcement of CV disease illness scripts, hypothesis-driven data gathering practice, ECG interpretation, and applying knowledge and skills in a realistic context. Discussion SP encounters representing CV conditions can effectively provide opportunities for students to integrate basic science knowledge and clinical skills. Students assessed the activity as helpful and engaging.